Acquaintance on HIV/AIDS among the Higher Secondary Level Students of Manikgonj District, Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: HIV (Human Immunodeficiency Virus) is a transmissible retrovirus that causes AIDS (Acquired Immune Deficiency Syndrome) in human, HIV infection gradually affects the immune system of human body and consecutively damages the cell. The result of HIV infection is relentless destruction of the immune system leading to the onset of Acquired Immunodeficiency Syndrome (AIDS). As young adults are one of the vulnerable groups for infection of HIV and studies regarding the awareness on HIV/AIDS among the young adults out of Dhaka are very few in numbers so this study was conducted outside of the capital among the higher secondary level students.Objective: To assess the level of awareness on HIV/AIDS among the higher secondary level students of Manikgonj District, Bangladesh.Materials and Methods: This observational study was carried out to observe the awareness of HIV/AIDS among the higher secondary level students of randomly selected urban and rural areas of Manikgonj District, Bangladesh. The total number of respondents was 246 and ages ranged from 16 to 25 years.Results: A total of 246 respondents were interviewed and among them the majority of students were male and awareness was high among the male respondents. Majority of the respondents (98%) heard about HIV/ AIDS. It also revealed 88.62% participants believed that it is a preventable disease and 78.50% of the respondents had knowledge about the unavailability of the vaccine. About the transmission, 93.90% respondents opined that it was due to infected blood transfusion; followed by 92.82% believed due to unprotected sex and 67.1% stated contaminated instruments cause transmission of HIV. In case of prevention of the disease, 88.21% believed health education as one of the preventive methods followed by using condom 86.59%, safe blood transfusion 80.49% and avoiding contaminated instrument 74.80%.Conclusion: The level of awareness among the higher secondary level students in study area Manikgonj, Bangladesh was satisfactory. To maintain this adequate focus should be given on the need for the further information, education and communication programs to identify the barriers and to seek the ways to enlighten the population about HIV/AIDS knowledge.Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 111-116